Individual physiological responses to changes in shoe bending stiffness: a cluster analysis study on 96 runners - Chollet, M.; Michelet, S.; Horvais, N.; Pavailler, S.; Giandolini, M. (European Journal of Applied Physiology, 2023)
Background Shoe longitudinal bending stiffness is known to influence running economy (RE). Recent studies showed divergent results ranging from 3% deterioration to 3% improvement in RE when bending stiffness increases. The variability of these results highlights inter-individual differences. Thus, our purpose was to study the runner-specific metabolic responses to changes in shoe bending stiffness.